If x and y are real values such that 0 ∘ ≤ x − y ≤ 1 8 0 ∘ and
sin x + sin y cos x + cos y = 1 , = 2 ,
what is the value (in degrees) of x − y ?
This problem is posed by Josh P .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rewrite the first equation as
2 sin ( 2 x + y ) cos ( 2 x − y ) = 1 ( ∗ )
And similarly the second one,
2 cos ( 2 x + y ) cos ( 2 x − y ) = 2 ( ∗ ∗ )
Now divide both the equations to get,
tan ( 2 x + y ) = 2 1
⇒ x + y = 2 arctan ( 2 1 ) = 2 arcsin ( 3 1 )
Substitute the above value of x + y in ( ∗ ) ,
⇒ 2 ⋅ 3 1 cos ( 2 x − y ) = 1
⇒ cos ( 2 x − y ) = 2 3
⇒ x − y = 6 0 ∘
Hence, the answer is 6 0 degrees.
Nice! I used the other more common method of squaring and adding.
By squaring the two equations, we get:
sin 2 x + sin 2 y + 2 sin x sin y = 1 ,
cos 2 x + cos 2 y + 2 cos x cos y = 2 ,
by summing them, we get:
sin 2 x + cos 2 x + sin 2 y + cos 2 y + 2 sin x sin y + 2 cos x cos y = 3
since: sin 2 θ + cos 2 θ = 1 for any angle θ , therefore:
2 + 2 sin x sin y + 2 cos x cos y = 3 ,
since:
sin u sin v = 2 1 ( cos ( u − v ) − cos ( u + v ) )
cos u cos v = 2 1 ( cos ( u − v ) + cos ( u + v ) )
for any angles u and v , therefore:
2 + cos ( x − y ) − cos ( x + y ) + cos ( x − y ) + cos ( x + y ) = 3 ,
2 cos ( x − y ) = 1 ,
cos ( x − y ) = 2 1 ,
and cos ( 6 0 ° ) = 2 1 , therefore the answer is 6 0 °
Squaring the first and second equation gives:
sin 2 x + 2 sin x sin y + sin 2 y = 1 cos x + 2 cos x cos y + cos 2 y = 2
Adding both equation yields:
sin 2 x + cos 2 x + 2 cos x cos y + 2 sin x sin y + sin 2 y + cos 2 y = 3 2 + 2 cos x cos y + 2 sin x sin y = 3 2 ( cos x cos y + sin x sin y ) = 1 cos x cos y + sin x sin y = 2 1 cos ( x − y ) = 2 1
Since 0 ∘ ≤ x − y ≤ 1 8 0 ∘ , x − y can only be equal to 6 0 ∘ .
there's a little mistake..
Typo: cos x cos y + 2 sin x sin y = 2 1 should be cos x cos y + sin x sin y = 2 1 .
sin 2 x + sin 2 y + 2 sin x sin y = 1 cos 2 x + c o s 2 y + 2 cos x cos y = 2 sin 2 x + sin 2 y + 2 sin x sin y + cos 2 x + c o s 2 y + 2 cos x cos y = 3 2 sin x sin y + 2 cos x cos y = cos ( x − y ) = 2 1
Therefore, x − y = 6 0
You didn't fully justify why x − y = 6 0 . cos ( α ) = 2 1 when α is some multiple of 360 degrees away from 60 degrees, not just 60 degrees. However, from the problem statement that 0 ≤ x − y ≤ 1 8 0 , it becomes clear that the only feasible solution is 60 degrees, so I guess it's not necessary.
One way to look at it is how we should get x-y from trigonometric identities we know. Recall that cos(x-y)=cosxcosy+sinxsiny. So we need to find a way to end up with this term from the given equations.
Square the first equation --> (sinx)^2+2sinxsiny+(siny)^2=1
Square the 2nd equation --> (cosx)^2+2cosxcosy+(cosy)^2=2
then add the two equations:
(sinx)^2+ (cosx)^2+2sinxsiny+2cosxcosy+(cosy)^2+(siny)^2=3
1+2cos(x-y)+1=3
x-y=60
[sin(x) + sin(y)^2 = sin^2(x) + 2sin(x)sin(y) + sin^2(y) = 1. [cos^2(x) + 2cos(x)cos(y) + cos^2(y) = 2. Adding these equations, and simplifying, 2[cos(x - y) = 1, cos(x - y) = 1/2, x - y = 60 degrees.]
{ sin x + sin y = 1 cos x + cos y = 2 . . . ( 1 ) . . . ( 2 )
{ ( 1 ) 2 : ( 2 ) 2 : sin 2 x + 2 sin x sin y + sin 2 y = 1 cos 2 x + 2 cos x cos y + cos 2 y = 2 . . . ( 1 a ) . . . ( 2 a )
( 1 a ) + ( 2 a ) : sin 2 x + cos 2 x + 2 sin x sin y + 2 cos x cos y + sin 2 y + cos 2 y 1 + 2 cos ( x − y ) + 1 ⟹ cos ( x − y ) x − y = 1 + 2 = 3 = 2 1 = 6 0 ∘
Square both the equation and add , we will get the following : cos(x) cos(y)+sin(x) sin(y)=1/2 =>cos(x-y)=1/2 =>x-y=60
Problem Loading...
Note Loading...
Set Loading...
Given the two equations sin x + sin y = 1 and cos x + cos y = 2 Squaring both the equations, ( sin x + sin y ) 2 = 1 ⇒ sin 2 x + 2 sin x sin y + sin 2 y = 1 − − − − − − 1 and ( cos x + cos y ) 2 = ( 2 ) 2 ⇒ cos 2 x + 2 cos x cos y + cos 2 y = 2 − − − − − − 2 Adding the two equations we get, sin 2 x + sin 2 y + 2 sin x sin y + cos 2 x + 2 cos x cos y + cos 2 y = 3 ⇒ ( sin 2 x + cos 2 x ) + ( sin 2 y + cos 2 y ) + 2 sin x sin y + 2 cos x cos y = 3 ⇒ 1 + 1 + 2 sin x sin y + 2 cos x cos y = 3 ⇒ + 2 sin x sin y + 2 cos x cos y = 1 ⇒ cos ( x − y ) − cos ( x + y ) + cos ( x + y ) + cos ( x − y ) = 1 ⇒ 2 cos ( x − y ) = 1 ⇒ cos ( x − y ) = 2 1 ⇒ ( x − y ) = 6 0 ∘